Zoroastrian origins for some Jewish beliefs and the similarity between them - Aboud Sammar, Saad; Khammat Kareem , mustafa (Journal of College of Education, 2021)
This study sheds light on the most important matters between the two religions، Judaism and Zoroastrianism، and the similarities between them، and perhaps there is an influence and influence of one religion on the other as a result of the friction of the two societies with each other، in addition to that there are similarities in some of the beliefs in both religions.